Interactions between the flame and different coatings in a slit burner. (1st October 2019) - Li, Fan; Yang, Haolin; Huo, Jiepeng; Wang, Xiaohan; Jiang, Liqiao; Zeng, Xiaojun; Zhao, Daiqing
Highlights: The interactions between flame and coatings were experimentally studied. The near-wall OH radical distributions were captured in a slit burner. Alumina coating improved flame stability, while AlCrN coating dose the opposite. The properties of AlCrN coating were slightly altered by the action of flame. The flame-wall chemical interaction was analyzed with surface analysis. Abstract: To improve the lifetime and the flame stability of combustion-based micro devices, two coating materials (AlCrN and alumina) are deposited on STS 304 substrate to investigate the interactions between the premixed n -butane/air flame and the solid walls heated to different temperatures in a slit burner. The flame-wall interaction is characterized by the measurements of quenching distance, flame pulsation and OH intensity distribution. Results show that the alumina coating sustains a shorter quenching distance compared with the STS 304 plate at an identical wall temperature, whereas the AlCrN coating exhibits a larger one. The highest near-wall OH intensity is observed in the alumina-coated wall, while the lowest is observed in the AlCrN-coated wall, indicating a correlation between the near-wall OH distribution and the quenching distance. When the channel gap is reduced to a critical value, the stable flame is converted into a pulsating flame, and the pulsation frequency monotonously increases as the wall temperature increases. Surface analysis reveals that the adsorbed oxygen on the surface may play an important role in flame quenching characteristics by affecting the OH intensity close to the wall surface. In addition, the flame exerts varying degrees of influence on the coating stability, surface structure, and elemental composition. The alumina coating maintains excellent thermal and chemical stability and can be used for surface optimization of static components. In contrast, although the AlCrN coating undergoes slight changes in structure and composition under the action of flame, it may still be a surface optimization option for moving parts without a significant increase in quenching distance.